Prenatal Exposure to Perfluoroalkyl Substances and Adiposity in Early and Mid-Childhood - Mora, Ana María; Oken, Emily; Rifas-Shiman, Sheryl L.; Webster, Thomas F.; Gillman, Matthew W.; Calafat, Antonia M.; Ye, Xiaoyun; Sagiv, Sharon K. (Environmental health perspectives, 2017)
Few studies have examined whether prenatal exposure to perfluoroalkyl substances (PFASs) is associated with childhood adiposity. We examined associations of prenatal exposure to PFASs with adiposity in early and mid-childhood. We measured plasma PFAS concentrations in 1,645 pregnant women (median, 9.6 weeks gestation) enrolled in Project Viva, a prospective pre-birth cohort study in Massachusetts (USA), between 1999 and 2002. We assessed overall and central adiposity in 1,006 children in early childhood (median, 3.2 years) and 876 in mid-childhood (median, 7.7 years) using anthropometric and dual X-ray absorptiometry (DXA) measurements. We fitted multivariable linear regression models to estimate exposure-outcome associations and evaluated effect modification by child sex. Median (25-75th percentiles) prenatal plasma perfluorooctanoate (PFOA), perfluorooctane sulfonate (PFOS), perfluorohexane sulfonate (PFHxS), and perfluorononanoate (PFNA) concentrations in children assessed in early childhood were 5.6 (4.1-7.7), 24.8 (18.4-33.9), 2.4 (1.6-3.8), and 0.6 (0.5-0.9) ng/mL, respectively. Among girls, each interquartile range increment of prenatal PFOA concentrations was associated with 0.21 kg/m (95% CI: -0.05, 0.48) higher body mass index, 0.76 mm (95% CI: -0.17, 1.70) higher sum of subscapular and triceps skinfold thickness, and 0.17 kg/m (95% CI: -0.02, 0.36) higher DXA total fat mass index in mid-childhood. Similar associations were observed for PFOS, PFHxS, and PFNA. We observed null associations for boys and early-childhood adiposity measures. In this cohort, prenatal exposure to PFASs was associated with small increases in adiposity measurements in mid-childhood, but only among girls. Citation: Mora AM, Oken E, Rifas-Shiman SL, Webster TF, Gillman MW, Calafat AM, Ye X, Sagiv SK. 2017. Prenatal exposure to perfluoroalkyl substances and adiposity in early and mid-childhood. Environ Health Perspect 125:467-473; http://dx.doi.org/10.1289/EHP246.